Hosts steal the show - The Star, Charles Fernandez (2012)
UNIVERSITI Pertahanan Nasional Malaysia (UPNM) were crowned champions for achieving the best cumulative results throughout the MUDS trilegged run-bike-run challenge I held at the UPNM campus in Sungai Besi.